“Los recursos naturales para estimular la psicomotricidad fina en Educación Inicial” - Chiluisa Cando, Jhomayra Anabel (2023)
This project aimed to analyze natural resources as a pedagogical tool for the development of fine motor skills in children in Cotopaxi province, Pujilí canton, Tingo La Esperanza parish, for which the objective of diagnosing the use of natural resources in the fine psychomotor development of boys and girls between the ages of 4 and 5 from four educational institutions in the parish was set. The research methodology is based on a qualitative approach, using a documentary and field research modality, as well as the descriptive and thematic type of research; the methods used are inductive, and to obtain beneficial results, techniques such as interview and observation. The study population comprises 62 preschool boys and girls from the four educational institutions and four educators of the same academic level. The results made it possible to show that there is a low lack of knowledge on the part of the educators regarding the subject; the problem is forceful in the learning process since they do not allow children not to develop their cognitive, motor, social, affective skills generating knowledge deficits in the future to achieve beneficial results; it is intended to develop a proposal that aims to stimulate and strengthen fine motor skills by using natural resources as didactic material creatively considering the children's imagination in Cotopaxi province, Pujilí canton, Tingo La Esperanza parish.